Analgesic effect of topical sevoflurane on venous leg ulcer with intractable pain - Gerónimo-Pardo, M.; Martínez-Monsalve, A.; Martínez-Serrano, M. (Phlebologie, 2011)
We are presenting the case of a patient with a very painful venous ulcer for whom therapy with different analgesic combinations (including acetaminophen, metamizol, tramadol, morphine, fentanyl, buprenorphine, pregabal-in, gabapentin, as well as applications of lido-caine/prilocaine eutectic cream and infusion of epidural ropivacaine) was unsatisfactory. Analgesic control was finally achieved through applications of liquid sevoflurane to the wound, which resulted in immediate, intense, and long-lasting analgesia. To the patients satisfaction, the same response was obtained throughout the 16 days it took the ulcer to heal. The compassionate use of sevoflurane in this innovative and promising manner warrants further research to evaluate its efficacy and safety.
Keywords: Pain intractable; drug therapy; varicose ulcer; drug therapy; anesthetics; inhalation; therapeutic use; sevoflurane